SLEEVE GASTRECTOMY IN PATIENTS WITH MORBID OBESITY AND HIV - PINTO,José Máximo Costa (2016)
ABSTRACT Introduction: It is estimated that there are nearly 40 million people with the human immunodeficiency virus (HIV) worldwide. Due to the advent of antiretroviral drugs, it has been observed increasing in obesity and metabolic rates among patients undergoing treatment. Thus, numerous surgical therapies for weight loss are proposed for continuous improvement in health of patients with HIV, being the vertical gastrectomy an option for intact intestinal transit. Objective: To evaluate the applicability of the vertical gastrectomy in patients with morbid obesity and HIV. Methods: Was conducted a systematic review of the literature, in the electronic databases Scopus, Pubmed, Cinahl, Scielo, Cochrane and Lilacs, from 1998 to 2015. MeSH headings used in data collection were "Gastrectomy" and "Morbid obesity" being combined with the descriptor "HIV". Were found 2148 articles in Scopus, 1234 in PubMed and 784 in Cinahl. The articles were analyzed by the Jadad Quality Scale, being reduced to 40 articles, subsequently reassessed using an elaborated form by the Critical Appraisal Skills Programme (CASP), reaching 12 articles in the end. Conclusion: It was found that vertical gastrectomy constitutes a safe and effective method, with low mortality and low rate of postoperative complications, being recommended as surgical technique in patients with obesity, HIV and comorbidities.